2021
DOI: 10.36096/ijbes.v3i2.260
|View full text |Cite
|
Sign up to set email alerts
|

Does credit access matter for household livelihood diversification in Ethiopia?

Abstract: This study examines the effect of credit access on both agricultural and off-farm activities based on a household survey of 371 rural farmer respondents in Ethiopia.it was analyzed using a logistic regression model and statistical description. Findings demonstrated that the demographic factors; gender, age, level of education, and family size have a positive and significant effect on credit access. Agricultural credit access is impacted by each of the demographic variables as independent variables. On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…For a 5% level of precision, this means that when household credit access declines, the chance of rural household participation increases by 0.373. This standpoint was shared by Tsegay et al (2021), who saw negative influences from rural households' involvement in non-farm economic activities. However, it differs from Bereket &Zenebe (2011) andAshebir &Negussie (2016), who found that access to credit was substantial and good in terms of the decision to participate in nonfarm work.…”
Section: Factors Influence Farmer's Participation In Non-farm Activitiesmentioning
confidence: 99%
“…For a 5% level of precision, this means that when household credit access declines, the chance of rural household participation increases by 0.373. This standpoint was shared by Tsegay et al (2021), who saw negative influences from rural households' involvement in non-farm economic activities. However, it differs from Bereket &Zenebe (2011) andAshebir &Negussie (2016), who found that access to credit was substantial and good in terms of the decision to participate in nonfarm work.…”
Section: Factors Influence Farmer's Participation In Non-farm Activitiesmentioning
confidence: 99%